The Relationship Between Nailfold Microcirculation and Retinal Microcirculation in Healthy Subjects - Tian, Jiaxin; Xie, Yuan; Li, Meng; Oatts, Julius; Han, Ying; Yang, Yiquan; Shi, Yan; Sun, Yunxiao; Sang, Jinghong; Cao, Kai; Xin, Chen; Siloka, Labisi; et al. (Frontiers in Physiology, 2020)
Objective: To evaluate whether the nailfold microcirculation is associated with retinal microcirculation in healthy subjects. Methods: Fifty subjects without systematic and ocular diseases were enrolled. Thickness of peripapillary retinal nerve fiber layer (RNFL), vessel density (VD) of radial peripapillary capillaries (RPCs) and superficial capillary VD in macular zone were measured with optical coherence tomography angiography in left eyes. Nailfold microcirculation, including capillary density, avascular zones, dilated capillaries, and hemorrhages was examined on the fourth digit of each subjects nondominant (left) hand with nailfold capillaroscopy. Results: After adjustment for relatively systemic factors, multivariate regression analyses showed a significant direct relationship between RNFL thickness and nailfold capillary density (OR=1.09; p=0.046). RNFL thickness and RPCs VD were negatively correlated with nailfold avascular zones (OR=0.855; p=0.007; OR=0.596; p=0.010). Superficial vessel density of parafovea was negatively associated with dilated nailfold capillaries (OR=0.794; p=0.012). Conclusions:In healthy subjects, nailfold capillary lower density and abnormalities are associated with reduced RNFL thickness and retinal vessel density. The results provide a theoretical foundation for relevant studies on ocular diseases with microvascular abnormalities and could contribute to pathogenesis understanding in the future. Nailfold capillaroscopy and optical coherence tomography angiography have the potential to identify risk factors and improve accuracy of the early diagnosis and treatment of ocular diseases, even systemic diseases with any microvascular component in clinical practice.